Surgical teams' attitudes and views concerning the surgical safety checklist(TR) - GÜRKAN, AYSEL; KIRTIL, İNCİ; DİKMEN AYDIN, YEŞİM (My University, 2022)
Objective: This study was conducted to determine the surgical team members’ views and attitudes concerning the Surgical Safety ChecklistTurkey (SSCTR). Methods: This descriptive-cross-sectional study was conducted in nine education and research hospitals in Istanbul with 561 surgical clinic and operating room nurses, surgeons, anesthetists, and anesthetic technicians. Data were collected using an information form to determine the demographic and professional characteristics of surgical team members, their attitudes and views concerning SSCTR. Results: According to the participants’ responses, the use of SSCTR was compulsory in the institution of 98% of the participants, 95.2% believed that this checklist should be used for each patient because it was effective in preventing complications, and 78.4% considered that it increased patient safety, but only 57.8% reported that SSCTR was routinely used in daily practice. Although the participants who had received training on SSCTR comprised 69% of the sample, 50.8% thought that training meetings were not beneficial. The rate of compliance was the lowest for SSCTR item “Team members' introducing themselves” (32.7%) and the highest for “Confirmation of identity, surgery type, and surgical site of the patient” (95.3%). Conclusion: The study findings showed that SSCTR was not used regularly in half of the patients. It is recommended that regular trainings with the active participation of all team members to ensure the effective use of the checklist.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Tıbbi Ekoloji ve Hidroklimatoloji; Medicine; Health Sciences; Internal Medicine Sciences; Medical Ecology and Hydroclimatology; TIP, ARAŞTIRMA VE DENEYSEL; Klinik Tıp; Klinik Tıp (MED); MEDICINE, RESEARCH & EXPERIMENTAL; CLINICAL MEDICINE; Clinical Medicine (MED); Araştırma ve Teori; İncelemeler ve Referanslar (tıbbi); Research and Theory; Reviews and References (medical); Surgical safety checklist; patient safety; safe surgery; IMPLEMENTATION; COMPLICATIONS; MORBIDITY; MORTALITY; METAANALYSIS